2020
DOI: 10.1016/j.ridd.2020.103720
|View full text |Cite
|
Sign up to set email alerts
|

Do typically and atypically developing children learn and generalize novel names similarly: The role of conceptual distance during learning and at test

Abstract: There is a large body of evidence showing that comparison leads to better conceptualization and generalization of novel names than no-comparison settings in typically developing (TD) children (e.g., Gentner, 2010). So far, comparison situations have not been studied with children with intellectual disabilities (ID) (Chapman & Kay-Raining Bird, 2012). In the present research children with ID and TD children matched on mental age with the Ravens coloured progressive matrices RCPM (Raven, 1965) were tested in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…A large body of research has demonstrated the benefits of comparison designs for learning novel object names [38][39][40], adjectives [41], action verbs [42], relational nouns [43,44] (see [45] for a meta-analysis; [46] for a synthesis). Considerable attention has also been paid to the conditions under which comparisons lead to better learning and generalization.…”
Section: Novel Noun Generalization Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of research has demonstrated the benefits of comparison designs for learning novel object names [38][39][40], adjectives [41], action verbs [42], relational nouns [43,44] (see [45] for a meta-analysis; [46] for a synthesis). Considerable attention has also been paid to the conditions under which comparisons lead to better learning and generalization.…”
Section: Novel Noun Generalization Tasksmentioning
confidence: 99%
“…Considerable attention has also been paid to the conditions under which comparisons lead to better learning and generalization. For example, the effect of the number of items compared [37,44], the perceptual similarity between the learning stimuli [47], or the conceptual distance between them [48,49] have all been extensively studied.…”
Section: Novel Noun Generalization Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Cela peut s'expliquer par la dissociation entre l'âge chronologique et l'âge mental chez les adolescents et les adultes présentant une déficience intellectuelle. En effet, ces dernières ayant vécu plus longtemps ont eu pour un âge mental donné davantage d'opportunités d'étoffer leur lexique (voir aussi Witt et al 2020, pour un argument similaire). Au-delà de ce premier constat, il est intéressant de noter que l'effet positif de l'expérience éducationnelle et de l'expérience de vie n'est pas limité à une étiologie particulière de déficience intellectuelle, mais constitue un trait commun à la déficience intellectuelle transcendant les étiologies (Facon, 2008 ;.…”
Section: De L'influence De L'âge Mental Et De L'âge Chronologiqueunclassified
“…Quelques études abordent la question chez des personnes présentant une déficience intellectuelle, mais elles restent encore rares. Nous citerons ainsiZampini, Salvi et D'ordorico (2015) ou encoreWitt, Comblain & Thibaut (2020) qui suggèrent que l'organisation et le développement du lexique des enfants neurotypiques et présentant une déficience intellectuelle reposent sur les mêmes bases cognitives. Ces auteurs utilisent des tâches de généralisation d'association mots-objets et de mots-relations que nous ne décrirons pas ici.…”
unclassified